2020
DOI: 10.21203/rs.2.11018/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patients’ experiences of discontentment one year after total knee arthroplasty- A qualitative study

Abstract: Background Total knee arthroplasty is a common procedure with generally good results. However, there are still patients who are discontented without known explanation. Contentment and discontentment have previously been captured by quantitative designs, but there is a lack of qualitative studies regarding these patients’ experiences. Qualitative knowledge might be useful in creating strategies to decrease the discontentment rate. Methods Of the 348 patients who responded to a letter asking if they were content… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(44 citation statements)
references
References 49 publications
1
43
0
Order By: Relevance
“…Internationally, several studies investigated guidelines and (exercise) recommendations for postacute, postoperative physical therapy after UKA or TKA, but none of these studies provided (evidence on the) recovery recommendations for activities of daily life [ 32 , 33 , 34 , 35 ]. These findings are in line with the studies from Nouri et al [ 14 ] and Mahdi et al [ 13 ], who both showed that patients expressed the need for mutual guidelines and advice regarding return to daily activities. Given the finding that preoperative expectations are one of the main determinants to influence postoperative patient satisfaction, realistic and multidisciplinary recovery recommendations regarding resumption of daily life activities could improve patient satisfaction after surgery [ 19 , 23 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Internationally, several studies investigated guidelines and (exercise) recommendations for postacute, postoperative physical therapy after UKA or TKA, but none of these studies provided (evidence on the) recovery recommendations for activities of daily life [ 32 , 33 , 34 , 35 ]. These findings are in line with the studies from Nouri et al [ 14 ] and Mahdi et al [ 13 ], who both showed that patients expressed the need for mutual guidelines and advice regarding return to daily activities. Given the finding that preoperative expectations are one of the main determinants to influence postoperative patient satisfaction, realistic and multidisciplinary recovery recommendations regarding resumption of daily life activities could improve patient satisfaction after surgery [ 19 , 23 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…Despite the good clinical outcomes with significant pain relief and improved knee function in most patients who receive knee arthroplasty, approximately 20% of the patients are dissatisfied postoperatively [ 12 ]. In a recent study, Mahdi et al concluded that 6–30% of knee arthroplasty patients had unfulfilled expectations regarding their ability to resume daily activities after surgery [ 13 ]. From a study with interviews among 45 knee arthroplasty patients, it was concluded that patients received little guidance and support regarding the resumption of daily activities [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another possible explanation of increased anxiety may be due in part to the patients' awareness of the prosthesis. A prior qualitative study reported that some participants worry because their prosthesis feels foreign to their bodies and they fear that it could initiate an inflammatory response, induce a malignancy, or lead to more surgery (46).…”
Section: Discussionmentioning
confidence: 99%
“…However, surgeries for total joint replacement have long waiting lists in the UK [ 15 ], which means that these patients need to bear with their painful joint symptoms and live with lower QOL until the surgery. Moreover, evidence indicates that receiving joint-replacement surgery may not relieve all symptoms for some OA patients [ 16 , 17 ], and 18% of patients are discontented with the outcome [ 18 ]. These contradictory evidence-based results may make it difficult for patients with knee OA to decide what treatment to choose.…”
Section: Introductionmentioning
confidence: 99%